2017
DOI: 10.1007/s11130-016-0596-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Asteraceae (Achillea millefolium and Calendula officinalis) and Lamiaceae (Melissa officinalis and Origanum majorana) Plant Extracts

Abstract: Asteraceae (Achillea millefolium and Calendula officinalis) and Lamiaceae (Melissa officinalis and Origanum majorana) extracts were obtained by applying two sequential extraction processes: supercritical fluid extraction with carbon dioxide, followed by ultrasonic assisted extraction using green solvents (ethanol and ethanol:water 50:50). The extracts were analyzed in terms of the total content of phenolic compounds and the content of flavonoids; the volatile oil composition of supercritical extracts was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 40 publications
3
36
1
5
Order By: Relevance
“…majorana leaves have phenolic compounds like carvacrol, thymol methyl ether that help in the (García-Risco et al, 2017). Ursolic acid and carnosic acids are the other constituents of this plant.…”
Section: Origanum Majoranamentioning
confidence: 99%
“…majorana leaves have phenolic compounds like carvacrol, thymol methyl ether that help in the (García-Risco et al, 2017). Ursolic acid and carnosic acids are the other constituents of this plant.…”
Section: Origanum Majoranamentioning
confidence: 99%
“…Tanto los aceites esenciales de esta planta, los cuales se sabe que son ricos en productos como el α -Thujene, el α -pineno y el 1,8 cineol, también llamado eucaliptol; todos compuestos de tipo monoterpenos carac-terizados por ser volátiles; como los extractos ricos en otro tipo de compuestos como sesquiterpenos, triterpenos, flavonoides, cumarinas, quinonas, carotenoides, amino ácidos y compuestos fenólicos, así como el phartenolide, una lactona sesquiterpénica, hallada principalmente en las hojas de las asteráceas con actividad antiinflamatoria y antioxidante, aún mayor al ácido ascórbi-co (45)(46), han evidenciado actividades antioxidantes, antiinflamatorias, antimicrobianas en modelos in vitro, in vivo e incluso a nivel clínico (47)(48)(49)(50), permitiéndole ser uno de los productos empleados en salud para el manejo de las enfermedades descritas, entre otras.…”
Section: Discussionunclassified
“…The ultrasound-assisted extraction as an advanced extraction technique provides the higher extraction yield of about 34% compared to the conventional extraction technique [32]. García-Risco et al [11] confirmed that the extract obtained by using 50% (v/v) ethanol and the ultrasound-assisted extraction has a higher phenolic content than the extract prepared by using pure ethanol.…”
Section: Introductionmentioning
confidence: 98%
“…Therapeutic properties of the flower are attributed to various types of bioactive compounds, such as: flavonoids, tannins, saponosides, carotenoids, triterpene alcohols, polysaccharides, amino acids, and essential oils [2,[4][5][6]. The extract of pot marigold flower has the antioxidant [7][8][9][10][11][12], antimicrobial [13][14][15], anti-inflammatory [16,17], anticancer [18,19], spasmolytic [20], hepatoprotective, and rheumatic protective activities [21]. Due to the complex chemical content and broad spectrum of pharmacological activity, this plant material has an application in pharmaceutical and cosmetic industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation